2006
DOI: 10.1080/00016340600756920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic group psychoeducation and relaxation in treating fear of childbirth

Abstract: Group psychoeducation and relaxation exercises were well received and rated as very helpful. More cesarean section requests were withdrawn than in the comparison group and in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(150 citation statements)
references
References 38 publications
4
132
0
14
Order By: Relevance
“…26 Previous studies have shown that treatment for fear of childbirth is effective, 15,[27][28][29][30] and this study adds a new important result by showing a possible reduction in postpartum mental health problems. To achieve this reduction it is important to offer women with fear of childbirth or demand for caesarean section professional support during pregnancy, as these problems cannot be solved by operative care.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…26 Previous studies have shown that treatment for fear of childbirth is effective, 15,[27][28][29][30] and this study adds a new important result by showing a possible reduction in postpartum mental health problems. To achieve this reduction it is important to offer women with fear of childbirth or demand for caesarean section professional support during pregnancy, as these problems cannot be solved by operative care.…”
Section: Discussionmentioning
confidence: 62%
“…For example, in the study hospitals the women who show a fear of childbirth are sent for consultations in a specialist maternity clinic where they are treated by trained midwives, psychologists, obstetricians and with group psychoeducation. 15,27 In addition to this support, recognition of the problem and further referral for psychiatric consultation or to a clinical psychologist might have improved the mental well-being. Hence, we assume that the care and support they received during pregnancy may explain the fact that women with a fear of childbirth were at lower risk of needing postpartum psychiatric care than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging the woman with severe FOC to verbalize her thoughts about the upcoming birth could be one way to reveal individual needs and thus increase the probability of providing her with relevant care. In comparison, Saisto et al [40] showed that psychoeducation and training relaxation during pregnancy were successful methods for helping women with FOC, even ending up in withdrawals of requests for a caesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of childbirth fear in pregnancy are thought to influence women's decisions about birth mode. Previously Saisto et al [12] identified that in Sweden and the United Kingdom, between 7% and 22% of requests for CS were due to childbirth fear.…”
Section: Introductionmentioning
confidence: 99%